Beyond big data: Social media challenges and opportunities for understanding social perception of energy. (October 2019) - Li, Ruopu; Crowe, Jessica; Leifer, David; Zou, Lei; Schoof, Justin
Abstract: Social perception, i.e., public advocacy and sentiment, on various energy issues deeply affects our energy future. This type of information is traditionally collected through structured energy surveys and statistics, which is often cost-formidable and labor-intensive. As free communication platforms with massive amounts of public opinions, social media can be used as a new lens for examining the dynamics of social perception towards both fossil and renewable energy. Compared with energy surveys, the analytics of social media leverage crowd-sourced public opinions instead of those from a directed and targeted audience. Based on a preliminary pilot study, we compare Twitter-based data mining results with a recent survey in three regions with different historic ties to fossil and renewable energy. We identify the critical issues associated with social advocacy and sentiment over energy development and consumption, and summarize policy implications. Furthermore, we discuss opportunities and challenges of using social media for understanding energy-related public perception. We conclude that more social media research on energy-related perception may lead to an in-depth understanding of polarized social perception, social contexts of energy policies, and possible strategies of bridging the gaps in and expanding the energy market.